Analysis of the Features of the Genomic Organization of Plague Microbe Strains Suitable for the Creation of a New Attenuated Vaccine - A. V. Grigorievykh; N. O. Bochalgin; S. A. Vityazeva; R. I. Pescherova; G. B. Mukhturgin; V. I. Dubrovina; L. V. Mironova; S. V. Balakhonov (Эпидемиология и вакцинопрофилактика)
Relevance. To date, the specific prevention of plague remains the most effective measure to prevent to prevent the deterioration of the epidemiological situation for this especially dangerous infection in the territory of the Russian Federation. The development of new vaccine preparations created on the basis of avirulent strains of Yersinia pestis with specific genetic defects, can play a crucial importance in the issues of plague immunoprophylaxis.Aim. Determination and comparative analysis of the genomic organization of avirulent strains Y. pestis I-1, Y. pestis I-3536 and vaccine strain Y. pestis EV line NIIEG.Materials and methods. The features of the genetic structure of three Y. pestis strains were studied using plasmid screening and whole genome sequencing.Results and discussion. It was found that the Y. pestis I-1 and Y. pestis I-3536 strains, like Y. pestis EV, lack the chromosomal pgm region. Analysis the genome sequence of Y. pestis I-1 showed that this strain is devoid of the plasmid pMT1, while its individual genes were found in the chromosome structure and the unique 340 kb plasmid. It was revealed that the Y. pestis strain I-3536 lost the plasmid pCD1, however, fragments homologous to this plasmid were found in the structure of its genome.Conclusion. The data obtained allow us to recommend Y. pestis I-1 and Y. pestis I-3536 as the basis for the development of a modern live attenuated plague vaccine.